Constructing professional identity through self-reflection: A case study of Pattani pre-service teachers in Indonesia - Khoiriyah, Khoiriyah; Sahlan , Moh. (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Pre-service teachers’ (PSTs) reflective teaching practice has been seen as early professional growth. However, it has not delved yet into how Pattani PSTs as international students construct their professional identity through self-reflection. The study aims to investigate the Pattani PSTs constructing their professional identity through self-reflection, the role of self-reflection in shaping their professional identity, and the process of self-reflection impacting their identity as future teachers during the teaching practice program in Indonesia. This qualitative case study involved three PSTs from Pattani in Southern Thailand as research participants. The data were garnered from reflective journals, dialogic reflection, and teaching practice artefacts. The data from self-reflections were cross-checked and validated using interviews with three teacher mentors and one teacher educator, as well as their lesson plans. Data from reflective journals and interviews were analyzed thematically, while dialogic reflections were examined using appraisal analysis. The findings revealed three emerging themes: (1) retrospection and collaboration; (2) inner, outer, and interactive contemplations; and (3) envisioning teacher as a future career. The study suggests that for international PSTs, targeted pre-practicum training in intercultural communicative competence and local pedagogical knowledge is crucial to facilitate positive self-reflection and professional identity construction.